A genre analysis of information summaries of IPO prospectuses / Saiful Adli Bin Shamsul Tajri - Saiful Adli, Shamsul Tajri (2013)
The purpose of the study was to analyse the structure of information summaries of IPO prospectuses submitted to Bursa Malaysia. The framework of the study comprised Swales (1990), Bhatia (1993) and Hajibah Osman (2005). The investigation focused on uncovering the communicative purpose, rhetorical structure and linguistic devices of information summaries. In addition, visual analysis was conducted. An added feature to the study is an investigation of Move 9: Announcing Possible Risks. The corpus was derived from information summaries of IPO prospectuses submitted to Bursa Malaysia. Ten information summaries each from manufacturing and food and beverages were selected at random from Bursa Malaysia prepared with the assistance of investment advisers and the listed companies. The former comprise 15411 words in size while the latter is 17433 words in length. The whole corpus is 32844 words. The investigation revealed the communicative purpose as “to inform and to warn,” while, the rhetorical structure consists of ten moves. Linguistic devices are presented in realizing the moves such as in the use of Auxiliary Verbs and Passives. Visuals found are mainly tables in most moves especially in the Financial Highlight section. Lexical items specific to risks are presented in Move 9: Announcing Possible Risks. In conclusion, the study investigated information summaries and found nine moves. The moves were realized with the communicative purposes and linguistic devices including an analysis of visuals.